Flora of Wabaunsee county, Kansas - Maus, Pearl Marie (Kansas State University, 1928)
The work upon which this thesis is based was done in Wabaunsee County, Kansas, during the growing seasons of 1926-1927. It is my purpose to give in this paper a list of the specieis of plants in the county with some account of their distribution, habitat and time of first flowers or fruiting. As early as 1896, some collections were made in Wabaunsee County by J.B. Norton, C.L. Clothier and A.S. Hitchcock. Seemingly they were limited to the northern portion of the county.
Call number: LD2668 .T4 1928 M31
Keywords: Kansas; Wabaunsee county; Plants; Flora; Masters theses